PENGARUH PENERAPAN LEMBAR KERJA PESERTA DIDIK BERBASIS PENDEKATAN SAINTIFIK DALAM MODEL PEMBELAJARAN INQUIRY TERHADAP KOMPETENSI FISIKA PESERTA DIDIK KELAS X SMA NEGERI 13 PADANG - Kurnia Heru Pratama; Hidayati Hidayati; Ramli Ramli (Universitas Negeri Padang, 2017)
One of the factors that lead to the lowness of lerners competence is less interesting learning process. The use of rare learning media worksheets make learners become less active in learning procces. This study purpose to determine the effect of worksheets based scientific approach in inquiry learning model toward learners competence of class X SMA Negeri 13 Padang. Type of this research is a quasi-experimental design with randomized control group only design. The population was all learners of class X SMA Negeri 13 Padang, academic year 2016/2017. The sampling technique used is purposive sampling. The reseaarch instruments used in this study are competent sheet (to examine attitude competence), result of final test (to measure knowledge competence), and perfomance assesment sheet (to measure skill competence). Data analyzed by testing the equality of two average. The equality of two average test is only to calculate competence value of knowledge dan skill, while attitude competence value is determine using result data description from each meeting. The result showed the average value of learner at two classes are 83.33 and 80.00 for knowledge competence, 85.90 and 81.16 foe skill competence. t testing obtained alternative hypothesis is accept for knowledge competence. t’ testing obtained alternative hypothesis is accept for skill competence. the conclusion is hypothesis stated that there is a significant effect in application-based worksheets learners the scientific approach in inquiry learning model toward physics competence of learners class X SMA Negeri 13 Padang